2008
DOI: 10.1111/j.1365-2141.2008.07416.x
|View full text |Cite
|
Sign up to set email alerts
|

A large kindred with X‐linked neutropenia with an I294T mutation of the Wiskott‐Aldrich syndrome gene

Abstract: X-linked neutropenia (XLN, OMIM #300299) is a rare form of severe congenital neutropenia. It was originally described in a three-generation family with 5 affected members and with an L270P mutation in the GTP-ase binding domain (GBD) of the Wiskott-Aldrich-syndrome protein (WASP) (Devriendt, et al 2001). Here, we report and describe a large three-generation family with XLN, with 10 affected males and 8 female carriers. A c.882T>C WAS gene mutation was identified, resulting in an I294T mutation. The infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 16 publications
2
87
0
Order By: Relevance
“…Recently, several human WASp mutations have been identified that result in constitutive activation through disruption of the autoinhibitory conformation, resulting in a phenotype of myeloid cytopenia (30)(31)(32). In all cases, the levels of WASp within peripheral blood cells have been reported to be normal, but they have displayed cytoskeletal abnormalities associated with enhanced and delocalized actin polymerization (26,31).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several human WASp mutations have been identified that result in constitutive activation through disruption of the autoinhibitory conformation, resulting in a phenotype of myeloid cytopenia (30)(31)(32). In all cases, the levels of WASp within peripheral blood cells have been reported to be normal, but they have displayed cytoskeletal abnormalities associated with enhanced and delocalized actin polymerization (26,31).…”
Section: Discussionmentioning
confidence: 99%
“…Three novel mutations (L270P, S272P, and I294T) clustered within the GTPase binding domain of WASP were recently identified in patients with a severe congenital form of X-linked neutropenia (XLN; Devriendt et al, 2001;Ancliff et al, 2006;Beel et al, 2009). The L270P, S272P, and I294T mutations destroy the autoinhibited conformation of WASP and generate an unfolded protein with enhanced actinpolymerizing activity (Devriendt et al, 2001;Ancliff et al, 2006;Beel et al, 2009).…”
Section: Br Ief Definitive Repor Tmentioning
confidence: 99%
“…Contrasting to WAS and XLT wherein inactivating WASP mutations lead to absent or residual protein expression, activating WASP mutations that target the GBD and interfere with autoinhibition cause X-linked neutropenia (XLN, SCN-XL) [37][38][39]. Constitutively active WASP results in intensified and misplaced actin polymerization and results in defective mitosis and cytokinesis as well as apoptosis-prone proliferation, especially in myeloid lineages [40].…”
Section: X-linked Neutropeniamentioning
confidence: 99%